1984
DOI: 10.1128/aem.48.4.833-839.1984
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of marine microbial surface interactions

Abstract: The macromolecular surface components involved in intraspecific cell surface interactions of the green microalga Chlorella vulgaris and closely associated bacteria were investigated. The specific surface attachment between this alga and its associated bacteria is mediated by lectin-like macromolecules associated with the surfaces of these cells. The binding activity of these surface polymers was inhibited by specific simple sugars; this suggests the involvement of specific receptor-ligand binding sites on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The complexity of the situation is illustrated by observations on enhanced adhesion of Enteromeha zoospores by mixed microbial biofilms (Dillon et al 1989), although in other studies single species of bacteria inhibit attachment (Thomas and Allsopp 1983). Adhesion of Chlorella vulgaris to glass is enhanced by nondiffusible fractions isolated from seawater, bacterial cultures, and C h b rella itself (Tosteson and Corpe 1975, Iman et al 1984, Tosteson et al 1985). Gregarious settlement behavior has been noted for a number of marine organisms, particularly invertebrates, in which a number of proteinaceous chemical settlement signals (pheromones) has been identified (for reviews see Rittschof 1993, Clare 1995, Walker 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the situation is illustrated by observations on enhanced adhesion of Enteromeha zoospores by mixed microbial biofilms (Dillon et al 1989), although in other studies single species of bacteria inhibit attachment (Thomas and Allsopp 1983). Adhesion of Chlorella vulgaris to glass is enhanced by nondiffusible fractions isolated from seawater, bacterial cultures, and C h b rella itself (Tosteson and Corpe 1975, Iman et al 1984, Tosteson et al 1985). Gregarious settlement behavior has been noted for a number of marine organisms, particularly invertebrates, in which a number of proteinaceous chemical settlement signals (pheromones) has been identified (for reviews see Rittschof 1993, Clare 1995, Walker 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, bacterial exudates have been implicated in the attachment of Chlorella spp. to glass (6). The difference in results for axenic cultures of Pleurochloris pyrenoidosa observed by SEM and epifluorescence microscopy may be due to the use of different fixatives in the preparation of specimens for observation.…”
Section: Resultsmentioning
confidence: 96%
“…Surface-exposed glycoproteins on the flagella also interact directly with the substratum in settlement (Bloodgood and Workman 1984). Attachment behavior involves lectins or lectin-like molecules, and receptors at the cell surfaces in select microbial systems (Imam et al 1984). Specific biochemical recognition between a settling spore and bacterial cell surface or extracellular materials may underlie the enhanced attachment by species of unicellular green algae (Kirchman et al 1982, Imam et al 1984.…”
Section: Discussionmentioning
confidence: 99%
“…Attachment behavior involves lectins or lectin-like molecules, and receptors at the cell surfaces in select microbial systems (Imam et al 1984). Specific biochemical recognition between a settling spore and bacterial cell surface or extracellular materials may underlie the enhanced attachment by species of unicellular green algae (Kirchman et al 1982, Imam et al 1984. Mitchell and Kirchman (1984) showed that settlement of a unicellular, green alga on bacterial films could be inhibited by treatment of the films with lectins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation